Review of VÁZQUEZ ALONSO, V.J; La libertad del artista. Censuras, límites y cancelaciones, Athenaica, Sevilla, 2023 (Asamblea. Revista parlamentaria de la Asamblea de Madrid, 2023)
Rview of the book La libertad del artista, written by Lecturer Vázquez
Keywords: Artistic freedom; Freedom of speech; Censorship; Cancelation